Journal of Samuel Maclay - Maclay, Samuel (Penn State University Press, 2025)
The Journal of Samuel Maclay is one man’s account of a 1790 surveying expedition, commissioned by the Supreme Executive Council of Pennsylvania, to explore the newly purchased land in northwestern Pennsylvania, including the headwaters of the west branch of the Susquehanna, the Sinnemahoning, and the Allegheny Rivers. The journal, published in 1887 with ample historical annotations by John F. Meginness, provides a richly detailed record of Maclay’s travels in the “New Purchase” over five months, ending along the Juniata River in the Kishacoquillas Valley. It preserves both the physical landscape and the cultural milieu of the state between the American Revolution and the turn of the century, as seen through the eyes of an observant surveyor. Day-to-day details of dining and travel, as well as Maclay’s personal interjections, help establish the greater historical and cultural context of this pivotal era in Pennsylvania’s expansion.